INTEGRATION OF AGRIBUSINESS ECOSYSTEM TYPOLOGY AND LEADING EDUOURISM OF TELETUBIES HILL, TOMAGE DISTRICT, FAKFAK DISTRICT - Wahyudi Sugeng Santoso; Titis Istiqomah; Risyana Mirda; Rifda Fitriaty (Sean Institute, 2023)
The Tomage District has potential for huma fields which are known to the public as Teletubbies Hill because of its very exotic shape . The exoticism of Teletubies Hill is only limited to its potential and has not been able to manage its use as a superior agribusiness and environmental education tourism location in an integrated manner, to encourage increased community empowerment and economic resources for Fakfak district. The research aims to find a strategy for developing a typology of superior agribusiness and educational tourism ecosystems on Teletubies Hill as an important economic growth center for Fakfak district . The research was carried out during May – December 2023. The research method was descriptive with a combination approach of quantitative and qualitative analysis. Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. Test the validity and reliability of the data in a gradual and structured manner using a triangulation and role sharing approach. The research results are presented in the form of a spider web diagram which is equipped with illustrations of shift share gap values, Ishikawa diagrams, Pearson correlation analysis , and regression equation models obtained from the SPSS version 2.3 statistical tool.